Features of parents’ selection and efficiency of artificial hybridization of Canna L. - Matiashuk, Raisa; Mazura, Marina (ScienceRise: Biological Science, 2020)
Possibilities of artificial hybridization with the use of genotypes from different Cannes groups and the prospect of attracting introduced species for genetically breeding enrichment of the modern Cannes variety are considered. The purpose of the work was to select parental pairs for artificial hybridization of Canna for genetically-selective enrichment of its diversity for cultivation in the southern arid region of Ukraine (in Kryvyi Rih). The pollen fertility index of introduced species and varieties of different groups of Canna was used for the selection of parental pairs. Materials and Methods. The research was done on 7 species (C. tuerckheimii Kraenzi.; C. indica var. warscewiczii Nob. Tanaka; C. iridiflora Ruiz&Pav.; C. flacida Salisd.; C. indica var. edulis Ker Gawl.; C. indica var. coccinea Mill.; C. indica L.) and 28 varieties of Canna of this collectors' fund. Pollen was chosen in finishing phase of budding for the cytologic analysis and fertility was being defined by iodine reaction of starch, according to the approved method. Hybridization was brought into action using known techniques for Canna. Dates of artificial hybridization and times of castration of the flower have been set according to ecological and climatic conditions of the industrial region. Results. On the basis of cytogenetic analysis of pollen of introduced species and promising varieties of Canna, parental pairs for artificial hybridization for the purpose of genetically-selective enrichment of its diversity and obtaining specimens, suitable for cultivation in the steppe zone of Ukraine, in particular in the ecologically destabilized region were selected. The approach to the selection of the original forms of Canna for artificial hybridization on the basis of cytogenetic analysis of pollen is developed. Conclusions. According to the index of pollen quality (FI) in final period of bud formation prospective introduced species Сanna were marked for further usage as parental forms in hybridization schemes. The most effective combinations of crossings were found on the basis of performed artificial hybridization as promising introduced Canna varieties for steppe zone and industrial region of Ukraine. The most effective combinations were obtained when crossing among the varieties of the Crozy group. Two selection forms have been pointed out from the received fund of hybrid plants Canna as to the complex of ornamental characteristic and have been introduced to the collection fund for their further implementation in landscape gardening